The Baltic States : Estonia, Latvia and Lithuania. - Lane, Thomas (Postcommunist states and nations., 2013)
Since the end of the Cold War there has been an increased interest in the Baltics. The Baltic States brings together three titles, Estonia, Latvia and Lithuania, to provide a comprehensive and analytical guide integrating history, political science, economic development and contemporary events into one account. Since gaining their independence, each country has developed at its own pace with its own agenda and facing its own obstacles. The authors examine the tensions accompanying a post-communist return to Europe after the long years of separation and how each country has responded t.